Ethical questions of sustainability - Bécsi, Zsófia (POLARITIES, 2023)
First, we have to interpret sustainability on a philosophical basis in order to clarify our concepts and outline the problems. Creating this common language platform, we can turn to the practice as to the discussion of ethical aspects. The issue of responsibility cannot be discussed until we know to whom, to what and to what time frames it applies. Further-more, we must be able to place human in the ecological system and clarify its role in the processes.